Expression profile of messenger and micro RNAs related to the histaminergic system in patients with five subtypes of breast cancer - Sirek, Tomasz; Sirek, Agata; Opławski, Marcin; Boroń, Dariusz; Chalcarz, Michał; Ossowski, Piotr; Dziobek, Konrad; Zmarzły, Nikola; Strojny, Damian; Grabarek, Beniamin Oskar (Frontiers in Oncology, 2024)
Disparities in estrogen receptor (ER), progesterone receptor, human epidermal growth factor receptor 2 (HER2), and Ki67 proliferation indices facilitate the categorization of breast cancer into four principal subtypes: luminal A, luminal B, HER2-positive, and triple-negative breast cancer (TNBC). Preclinical studies investigating the therapeutic potential of histaminergic system targeting in breast cancer have shown promising results. This study aimed to assess the expression profiles of messenger ribonucleic acid (mRNA) and micro RNA (miRNA) related to the histaminergic system in five subtypes of breast cancer among Polish women. Patients with five breast cancer subtypes were included in the study: luminal A (n = 130), luminal B (n = 196, including HER2-, n =100; HER2+, n= 96), HER2+ (n = 36), and TNBC (n = 43). They underwent surgery during which the tumor tissue was removed along with a margin of healthy tissue (control material). Molecular analysis included the determination of a microarray profile of mRNAs and miRNAs associated with the histaminergic system, real-time polymerase chain reaction preceded by reverse transcription of selected genes, and determination of histamine receptors (human histamine H1 receptor [HRH1], human histamine H2 receptor [HRH2], and human histamine H4 receptor [HRH4]) using an enzyme-linked immunosorbent assay. Statistical analysis was performed with statistical significance at p < 0.05. Nine mRNAs were significantly differentiated in breast cancer sections, regardless of subtype, compared to control samples: HRH1, HRH2, HRH4, histamine N-methyltransferase (HNMT), 5-hydroxytryptamine receptor 6 (HTR6), endothelin 1 (EDN1), endothelin receptor type A (EDNRA), adenosine deaminase (ADA), solute carrier family 22 member 3 (SLC3A2). Predictive analysis showed that hsa-miR-34a potentially regulates HRH1 expression, whereas hsa-miR-3140-5p and hsa-miR-4251 potentially affect HRH2 expression. In contrast, HRH4 and EDN1 expression were regulated by hsa-miR-1-3p. The expression of HNMT is potentially regulated by one miRNA, hsa-miR-382, whereas EDNRA expression is regulated by two miRNA molecules: hsa-miR-34a and hsa-miR-16. In contrast, hsa-miR-650 is involved in the regulation of HTR6 expression, whereas hsa-miR-1275 potentially interacts with three mRNAs: ADA, SLC23A2, and HRH1. Molecular analysis confirmed that the selected mRNA and miRNA transcripts could be promising molecular markers and therapeutic targets.